Paul Among the Apocalypses?: An Evaluation of the 'Apocalyptic Paul' in the Context of Jewish and Christian Apocalyptic Literature - Davies, J. P. (The Library of New Testament Studies, 2016)
CONTENTS -- Acknowledgments -- Abbreviations -- Chapter 1 -- PERPLEXED BY THE "APOCALYPTIC PAUL"? -- 1. Introduction -- 2. Paul and Apocalyptic in Recent Study -- 3. Prolegomena -- 4. The Structure of This Book -- Chapter 2 -- EPISTEMOLOGY: REVELATION AND WISDOM -- 1. Introduction -- 2. Epistemological Dichotomies in the "Apocalyptic Paul" -- 3. Epistemological Duality in Jewish Apocalyptic Literature -- 4. Epistemological Duality in the Book of Revelation -- 5. Implications for the Epistemology of the "Apocalyptic Paul" -- Chapter 3 -- ESCHATOLOGY: "IRRUPTION" AND HISTORY -- 1. Introduction